The Terrorist Perspectives Project: strategic and operational views of Al Qaida and associated movements - Stout, Mark (Naval Institute Press)
Salafi jihadist theology and the making of a movement -- Enemy self-perceptions -- Intelligence: the hidden hand and iron fist -- AQAMs perception of its enemies -- Strategic adaptation in the global Salafi jihadist movement -- Current AQAM strategic thinking -- Strategic communication -- Joining the caravan -- Policy implications: so what and now what? -- Acronyms and abbreviations -- Glossary of Arabic terms